FUNGSI SEMANTIK KOSAKATA ALAT DAN TEKNIK PENANGKAPAN IKAN MASYARAKAT NELAYAN DI KAWASAN BOULEVARD MANADO - Lontoh, Irma Maria (Kajian Linguistik, 2018)
The purpose of this study is to describe the function of semantic vocabulary tools and fishing techniques in fisherman communities in the area of Boulevard Manado. This research uses qualitative descriptive method and uses lexical semantic study approach to analyze semantic function of vocabulary tool and fishing technique in fisherman communities. This research was conducted along the coastal area of Boulevard, Sario Sub-district, Manado City, North Sulawesi. Sources of data in this study were taken from those who work as fishermen, who know about the vocabulary tools and fishing techniques.The data collection techniques are direct observation techniques and interviews. The data collection tool was the researcher as a key instrument. Based on the results of data analysis research found in fishing gear and techniques in Bolevard Manado area, there are 30 vocabulary in fishing gear, and 14 vocabulary in fishing technique in the form of these results collected in this study. The researcher hopes for this research continued on the vocabulary of fisherman fishing tools and techniques in the Bolevard Manado area, from different perspectives, so that further research can complement the study of semantics, especially lexical semantics with other problems.                                              Keywords: Function of Semantic, vocabulary tools, fishing techniques ,Fisherman communities.